An assessment of the impacts of Industry 4.0 on aeronautical industry - Barbieri Ferreira, Marcos Jose (2020)
This paper seeks to discuss and evaluate the impacts of the group of innovations brought by industry 4.0 in the aeronautical sector. Were selected and conceptualized the main technologies with high possibility of transforming the aeronautical industry, indicating the transforming capacity of each one. As a result, it was defined a typology of impacts of these technologies in the various segments of the aviation industry looking qualify the changes in market structure: (i) negligible; (ii) small when there are new entrants; (iii) intermediate, when establishing a new business model and; (iv) large, when there is the creation of new product categories. In addition, we try to show the possibility of creating a new segment that will focus on providing urban air transport services for shared use, with the use of landing vehicles and vertical takeoff, electrical propulsion and autonomous driving, shaping the disruptive role of analyzed technologies.